The Influences of Sustainability Report and Corporate Governance toward Financial and Entity Market Performance with Political Visibility as Moderating Variable - Ingrid Panjaitan (Binus Business Review, 2017)
The aim of this research was to identify the effect of corporate governance and sustainability report on the financial performance of entities, and corporate governance and sustainability report on the market entity with political visibility as moderating variable. Sustainability report was measured by a dummy variable by the Corporate Governance Scorecard with Indonesian Institute for Corporate Directorship (IICD). Then, financial performance as measured by profitability ratio (ROA) and Liquidity Ratio (CR), as well as the market performance were measured using Tobin’s Q. Meanwhile, the political visibility was measured by the log of total assets. The analysis of the data used Path Analysis method with Structural Equation Modeling (SEM). The analysis shows four results by using political visibility as moderating variable. First, the quality of corporate governance affects the financial performance. Second, the quality of corporate governance influences Tobin’s Q. Third, the sustainability report has an effect on the Return on Assets and current ratio. Last, sustainability report also affects Tobin’s Q.